Factors on development of Community-Based Tourism (CBT) in Phitsanulok Province of Thailand - Witchayakawin, Pakin; Abdul Aziz, Yuhanis; Bali Mahomed, Anuar Shah; Abdullah, Nawal Hanim (Innovare Academics Sciences, 2020)
This qualitative research by case study approach focuses on identifying the factors on the development of community-based tourism (CBT) in Phitsanulok Province of Thailand. The in-depth interview is the primary tool, gathering data from 10 key informants who are community leaders, CBT and homestay operators as well as a CBT project founder from June to July 2019. Cluster random sampling technique was used in three dominant CBT villages in Phitsanulok Province. An open coding technique by Nvivo12PLUS program was used to analyze the data. The findings show that the seven most important factors covering community participation are: ownership, outside support and supportive policy, marketing, value creation and supply chain, empowerment and people potential, leadership, and partnership. Surprisingly, three new effective factors are entrepreneurship skill, type of activities, and tour package design. It implies that visitors could accommodate one more night in Phitsanulok due to the activity types that appear to be an effective factor in developing and encouraging their stay.